Sports participation and injury related to the COVID-19 pandemic: will data support observations from clinicians and athletes? - Tak, I.; Rutten, J.; van Goeverden, W.; Barendrecht, M. (BMJ Open Sport & Exercise Medicine, 2022)
The Dutch Sports Participation Index showed a dramatic decrease in sports participation over 2020 and 2021 of up to 15% per month in the total population aged 5-80 years.1 This decrease can be related to closure of sporting grounds and fitness centres, as well as the widespread advice to avoid live human interaction in striving to reduce the spread of coronavirus. Although many started a new type of sport or took part in unorganised physical activities, 22% were still less active than before the pandemic.1 Restricted sports participation is also associated with mental health issues, more in individual than in team sport athletes.